Analisis Implementasi P5 Dimensi Berakhlak Mulia Pada Siswa Kelas II SDN Pedurungan Lor 02 - Sari, Tri Hesti Puspita; Azizah, Mira; Purwaningrum, Monica Ratih (STKIP Andi Matappa Pangkep, 2024)
The implementation of the Pancasila Student Profile is important to shape the character of students in accordance with the values of Pancasila and prepare them as the next generation of the nation who are pious, reliable, professional, and highly ethical. This study aims to analyze how the implementation of the Pancasila Student Profile on the noble moral dimension of grade II students at SDN Pedurungan Lor 02. This study used a descriptive qualitative approach in the form of written words observed. This research involved teachers and grade II students of SDN Pedurungan Lor 02 Semarang City through field observation techniques, direct interviews as data sources, and documentation. The results of the study found that the implementation of P5 dimensions of noble morals in grade II SDN Pedurungan Lor 02 has gone well because some students have been able to develop noble moral characters optimally and are able to apply them in everyday life. However, some students still find a lack of self-awareness that requires additional motivation and lack of cooperation of all parents in carrying out these activities at home.